2018
DOI: 10.1039/c8ta03643h
|View full text |Cite
|
Sign up to set email alerts
|

Modulating oxygen vacancies in Sn-doped hematite film grown on silicon microwires for photoelectrochemical water oxidation

Abstract: Dual-absorber photoelectrodes are attractive candidates for solar water splitting due to their broadened absorption spectrum and improved photovoltage compared to single-absorber systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…the separation efficiency was the largest. 90 Even though one semicircle can be clearly observed in the Nyquist plots, two semicircles can be distinguished by enlarging the high frequency range: smaller one in the higher frequency region (1-100 kHz) and predominant one in the medium frequency region (0.1 Hz to 1 kHz). According to literature data, the higher frequency region semicircle is attributed to the charge transfers and recombination processes occurring at the electrode/electrolyte interface, while the medium frequency region semicircle is attributed to electrochemical processes occurring at the photoanode/redox electrolyte interface.…”
Section: The Inuence Of Ctab and F127 On The Photocatalytic Propertimentioning
confidence: 99%
See 1 more Smart Citation
“…the separation efficiency was the largest. 90 Even though one semicircle can be clearly observed in the Nyquist plots, two semicircles can be distinguished by enlarging the high frequency range: smaller one in the higher frequency region (1-100 kHz) and predominant one in the medium frequency region (0.1 Hz to 1 kHz). According to literature data, the higher frequency region semicircle is attributed to the charge transfers and recombination processes occurring at the electrode/electrolyte interface, while the medium frequency region semicircle is attributed to electrochemical processes occurring at the photoanode/redox electrolyte interface.…”
Section: The Inuence Of Ctab and F127 On The Photocatalytic Propertimentioning
confidence: 99%
“…To explain the effects of the surfactants, i.e. surface-to-bulk defects ratio on the photoresponse and charge transport phenomena, 90,91 Nyquist plots for the three ZnO photoanodes were recorded in dark and under illumination, at the potential of 1.5 V vs. SCE. The Nyquist plots display similar semicircles with different radii, Fig.…”
Section: The Inuence Of Ctab and F127 On The Photocatalytic Propertimentioning
confidence: 99%
“…Until now, various dopants, including Ti [16], Co [18], Mo [17], Zn [19], Bi [13], Ni [18], Nb [20], Cu [18], Al [21], Ta [22], Fe [23-25], Te [26], and Ba [27], have been employed to alter the structural, optical, electrical, and band edge properties of WO 3 and to enhance its photocatalytic properties. Previously, Sn has been actively used as an effective dopant material for metal oxides, such as Fe 2 O 3 , to enhance its PEC water splitting properties [28,29], revealing its positive impact as a dopant material. Moreover, a detailed literature survey revealed that despite a few reports, no in-depth study has been reported regarding the synthesis and PEC properties Sn-doped WO 3 thin films.…”
mentioning
confidence: 99%
“…The reason can be explained by the advantage of Ge as a dopant in hematite, including the feasible atomic radius of Ge, and the low formation enthalpy of the secondary phase of GeO2 as previously reported 27 .…”
Section: Pec Water Oxidation Activity and Characterizationmentioning
confidence: 65%
“…Doping to improve the poor charge transfer behavior is one of the most powerful strategies that has been suggested to address these notable drawbacks 10,[18][19][20][21][22][23][24][25] . But even when Si 22,23,26 , Sn 18,19,27,28 and Ti 20,21,[29][30][31][32] atoms were broadly utilized as representative dopants, the hematite photoanode doped with these heteroatoms still exhibited low conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%